A Review on Bhaishajya Kaal mentioned in Astang Hridya - Choudhary, Amit; Dudi, Sunita; Kotecha, Mita; Bhatnagar, Shailza (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda being a life science emphasizes to maintain healthy life and cure of diseases. The effectiveness of Ayurveda drugs depends on the administration time (Bhaishajya Kaal) and it is described very well in Ayurveda classics. In Ayurveda there are many key factors which helps to fulfill its aim. Administering drug at proper time is also such unique concept in treating disease whom we can’t neglect. In Ayurveda texts Bhaishajya Kaal is described in relation to food, they are intended for Shamana Chikitsa only and the root of administration to all Kaal is oral. An attempt is being made in this article to review and understand the way of enhancing therapeutic action of drug by Bhaishajya Kaal described in Astang Hridya.